Amorphous silica biomineralizations as a silicon source and its role on the nutrient and micronutrients dynamics on southeastern Buenos Aires agroecosystems - Frayssinet, Celia (2019)
Silicon (Si) in soil proceeds from minerals of lithogenic origin and amorphous silica biomineralizations. Grasses are the main producers of these biomineralizations, known as silicophytoliths. Recently, Si has been recognized as a beneficial element, being important for the agricultural sustainability and environmental preservation. Southeastern Buenos Aires has Argiudolls, characterized by its high fertility and aptitude for crop development. Ultimately, the agricultural practices had been grown and, consequently, the level of soil degradation has been improved, due to the increase in the content of trace metals (MT), and the decrease of nutrient contents, among others. The aim of this work was to analyze the Si effects on the phosphorus and heavy metals contents in the soil-crop system. To that purpose, Si fertilizers were applied to the soil before sowing the wheat plants. Soil and plant samples were taken on September and December. Si content, available phosphorus (P) and HM ((Cu, Cd, Pb, Mn, Zn, Fe, Ni, Cr) contents were determined in soil solution, as well as the silicophytoliths and HM contents on different organs of the plant material (leaf, stem and infructescence), all them through standard methodologies. In soil solution an inverse relationship between Si and P was observed (Si increases 215umol/L while P decreases 7ppm ), as well as between Si and HM ( Si raised 13mg/L Si while HM dropped 0.24mg/L). On wheat plants there was a positive relation between silicophytoliths and HM contents registered (augment of 193mg/g silicophytoliths and 129ug/g HM, respectively). Is worth nothing that the values obtained here are between those allowed by FAO and UE. Concluding, Si could improve the P bioavailability for the crop and also some phytoremediation processes, as it diminishes de HM content in the soil solution and promotes their capture by the plant but without trespassing the threshold values, which allow the farmers to continue with its economic exploitation as usual. Thus, will be relevant to continue evaluating the Si application, since it would improve the development of a sustainable and profitable agriculture.